Mengubah Pemahaman Konsep Istikharah Dari Bertanya Menuju Berserah Diri - Alexa Ayu Dewanda; Intan Nuraini Azzahra; Hanestesia Zahara; Wismanto Wismanto; Resya Eka Putri (CV. Aksara Global, 2024)
This article is an interpretive study of the Istikharah prayer taught by the Prophet Muhammad SAW as mentioned in several hadith histories. Through the content analysis method, the author tries to examine the meaning of prayer using descriptive analysis methods. From this analysis, information was obtained that there must be a change in understanding of the concept of Istikharah which is often understood as a form of